Endozoochory by the cooperation between beetles and ants in the holoparasitic plant Cynomorium songaricum in the deserts of Northwest China. - Zhi Wang; Huan Guan; Bingzhen Li; Qianqian Zhang; Qing Chen; Dehui Wang; Kexin He; Zikang Jin; Guilin Chen (PLoS ONE)
Cynomorium songaricum Rupr. first described by Carl Johann (Ivanovič) Ruprecht in 1840 is a desert parasitic plant that mainly parasitizes the roots of Nitraria L. (especially of Nitraria tangutorum Bobrov., Nitraria sibirica Pall.). During seed maturation, C. songaricum releases a distinct smell, and its seeds are round and dust-like. Previous studies indicated that most parasitic plants produce small seeds, which are primarily dispersed by the wind. Recent studies reveal the significant role of animals in the seed dispersal of parasitic plants. In this study, we combined (1) the direct observation of the seed dispersal of C. songaricum, and (2) the indoor breeding of beetles and ants to assess the viability of seeds, clarify the seed dispersal system, and explore the mechanisms by which the seeds attract dispersal agents. By a population study, we identified beetles (Mantichorula semenowi Reitter, 1888) and ants (Messor desertora He & Song, 2009) as the primary seed dispersal agents for the C. songaricum. These plants rely on the visits from these agents to transfer their seeds near the roots of the host plant, Nitraria L.. The release of a distinct volatile compound from C. songaricum seeds attracts M. semenowi and M. desertora to consume and/or transport the seeds. This study provides the first evidence of a multi-medium and inter-species seed dispersal system in the C. songaricum. This study elucidates the role of invertebrates in the seed dispersal of desert parasitic plants. We propose that the two seed dispersal agents play distinct roles in the sequential seed dispersal of C. songaricum, representing two key stages in the overall seed dispersal mechanism.